Czy logiczna możliwość implikuje metafizyczną możliwość? - Paweł J. Zięba (Zagadnienia Filozoficzne w Nauce, 2014)
According to Chalmers, the argument from the conceivability of philosophical zombies disproves materialism in the philosophy of mind. This claim depends on the assumption that conceivability (logical possibility) entails metaphysical possibility. Such entailment is incorrect, however, because a materialist might formulate an analogous argument from the conceivability of anti-zombies. A clash between two mutually excluding logical possibilities prevents one from inferring a metaphysical possibility from any of them.